Laser-Induced Tunable White Light Emission in Yb3+/Er3+/Tm3+ Ion-Doped La2Ti2O7 - (:unkn) unknown (My University, 2023)
A series of compounds with the general formula (La1−xREx)2Ti2O7 (x = 0.005, 0.015, and 0.025) doped with Yb3+, Er3+, and Tm3+ rare Earth ions were prepared by the traditional solid-state reaction at 1350 °C for 24 h. The X-ray powder diffraction technique, high-resolution transmission electron microscopy, and photoluminescence spectroscopy technique were used to characterize the structure and optical properties of the compounds. All compounds showed a single-phase orthorhombic structure with a space group Pna2 1, as confirmed by JCPDS (Cart No: 01-070-1690). The La1.9Yb0.04Er0.01Tm0.05 Ti2O7 nanocrystals exhibited intense tunable white light luminescence signals in the full spectrum, and green and blue emissions were predominant in the Yb3+/Er3+− and Yb3+/Tm3+-doped titanates, respectively. In this study, the influence of concentration and excitation power on the upconversion luminescence, color, and calculated laser-power-induced heating performance of La2Ti2O7 nanophosphors were investigated at room temperature.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Temel Bilimler (SCI); FİZİK, YOĞUN MADDE; Natural Sciences (SCI); PHYSICS; PHYSICS, CONDENSED MATTER; Elektronik, Optik ve Manyetik Malzemeler; Fizik Bilimleri; Electronic, Optical and Magnetic Materials; Physical Sciences